ATTEC: a potential new approach to target proteinopathies. Issue 1 (2nd January 2020) - Li, Zhaoyang; Zhu, Chenggang; Ding, Yu; Fei, Yiyan; Lu, Boxun
ABSTRACT: Many diseases are caused by aberrant accumulation of certain proteins that are misfolded and cytotoxic, and lowering the level of these proteins provides promising treatment strategies for these diseases. We hypothesized that compounds that interact with both the disease-causing protein and the phagophore (autophagosome precursor) protein LC3 may tether the former to phagophores for subsequent autophagic degradation. If true, this a ut ophagosome-te thering c ompound (ATTEC) concept could be applied to many disease-causing proteins to treat diseases. We tested this hypothesis in the scenario of Huntington disease (HD), a neurodegenerative disorder that is caused by the mutant HTT (mHTT) protein with an expanded polyglutamine (polyQ) stretch. In our recent study, we designed a small-molecule microarray-based screening and identified four mHTT-lowering compounds that interact with both mHTT and LC3, but not wild-type (WT) HTT. These compounds target mHTT to phagophores for autophagic degradation without influencing the WT HTT level, and rescue HD-relevant phenotypes in HD cells and in vivo in the fly and mouse HD models. Interestingly, these compounds interact with the expanded polyQ stretch directly and are able to reduce other disease-causing proteins with expanded polyQ. In summary, our study provides the initial validation of lowering mHTT by ATTEC, providing entry points to new treatment strategies of HD and similar diseases.